The Biosimilar Landscape: An Overview of Regulatory Approvals by the EMA and FDA - Ioana Gherghescu; M. Begoña Delgado-Charro (MDPI AG, 2020)
Biosimilar medicines expand the biotherapeutic market and improve patient access. This work looked into the landscape of the European and US biosimilar products, their regulatory authorization, market availability, and clinical evaluation undergone prior to the regulatory approval. European Medicines Agency (EMEA, currently EMA) and Food and Drug Administration (FDA) repositories were searched to identify all biosimilar medicines approved before December 2019. Adalimumab biosimilars, and particularly their clinical evaluations, were used as a case study. In the past 13 years, the EMA has received 65 marketing authorization applications for biosimilar medicines with 55 approved biosimilars available in the EU market. Since the first biosimilar approval in 2015, the FDA has granted 26 approvals for biosimilars with only 11 being currently on the US market. Five adalimumab biosimilars have been approved in the EU and commercialized as eight different medicines through duplicate marketing authorizations. Whilst three of these are FDA-approved, the first adalimumab biosimilar will not be marketed in the US until 2023 due to Humira's exclusivity period. The EU biosimilar market has developed faster than its US counterpart, as the latter is probably challenged by a series of patents and exclusivity periods protecting the bio-originator medicines, an issue addressed by the US's latest 'Biosimilar Action Plan'.